ANALISIS POTENSI RAWA CERMAI KECAMATAN PALOH KABUPATEN SAMBAS KALIMANTAN BARAT - Anugrah Isromi, - (2009)
POTENTIAL ANALYSIS OF CERMAI SWAMPLAND, IN PALOH SUB-DISTRICT SAMBAS DISTRICT WEST BORNEO By : Anugrah Isromi / 056671, 2009 The research driven by the curiosity to know the social economy's state of the citizen around reclamation area, Cermai swampland, considered that the swampland has been a field cultivating by the community. Therefore, the research problems are (1) How is the physical state and the cultivation of Cermai Swampland did by the citizen in Paloh sub-district, (2) How many outcome and productivity rate of agriculture commodity in Cermai Swampland, Paloh sub-district, (3) How is the social economy state of the citizen in Cermai Swampland, Paloh sub-district. The method of this research is survey method with the population of: (1) The whole villages in Paloh sub-district, (2) The whole citizens in Paloh sub-district, while the sample included : (1) two villages in Paloh sub-district, Nibung and Sebubus, (2) 100 numbers of citizen which the data gain by carrying out questionnaire and interview. In this research, the sample method used probability sampling, while the technique is cluster sampling. Cluster sampling is a technique to make larger areas being a smaller unit, with the same quantity. Instead, the smaller unit of areas is not taken as a whole sample. Cluster sampling is chosen because of the larger areas of the research, with the relatively homogeny state. The independent variable consists of : (1) cultivation of swampland, (2) the productivity and outcome of agriculture commodity, and the dependent variable is social economy's state of the citizen and the physical condition. The data collecting technique and instrument used in this research are field observation with systematically way of observation by using a guideline, interview with independent guide interview system by using a guideline, questionnaire, library research and documentation. The data analysis technique includes calculation by using Spearman and Eta's formula. The result of the research showed that there are a few fields cultivating in Cermai Swampland, still there are great amount of forests and bushes, accounting of 12 % for the agriculture field and 82 % for forests and bushes. Based on the agricultural outcome , the average productivity is 1-3 ton in one time of yield, with the average result of Rp.500.000,-. The citizen's income level is still low, because it lies on the UMR rate of the area. Citizen's composition based on their education level showed that more of them are in elementary school rate, but for their responsibility (children) are in senior high school rate and higher education rate which is still low.